Choosing Wisely in radiation therapy for breast cancer: Time lag in adoption of hypofractionated radiation therapy in Victoria. Issue 2 (16th February 2021) - Ong, Wee Loon; Khor, Richard; Chao, Michael; Milne, Roger L; Millar, Jeremy; Foroudi, Farshad
Abstract: Introduction: To evaluate the adoption of hypofractionated radiotherapy (HFRT) for breast cancer (BC) in Victoria, Australia. Methods: This is a population‐based cohort of women with BC who had breast RT as captured in the Victorian Radiotherapy Minimum Data Set between 2012 and 2017. We defined HFRT as < 25 fractions of RT. The pattern of HFRT use over time was evaluated with the Cochrane–Armitage test for trend. Factors associated with HFRT were identified using multivariable logistic regression. Results: 12, 717 women were included in the study. Overall, 6, 653 (52%) patients had HFRT. HFRT use increased from 35% in 2012 to 66% in 2017 ( P ‐trend < 0.001). Older women were more likely to have HFRT (74% for women aged ≥ 70 years vs. 27% for women aged < 50 years; P < 0.001). Women who had nodal irradiation were less likely to have HFRT compared with those who did not (13% vs. 57%; P < 0.001). HFRT use was more common in public than private institutions (57% vs. 46%, P < 0.001), and in metropolitan than regional centres (54% vs. 46%, P < 0.001). In multivariable analyses, the progressive increase in HFRT use over time was independent of other covariates – women treated in 2017 were 7.3 times (95% CI = 6.3–8.6, P < 0.001) more likely to be treated with HFRT than in 2012. Age at RT, nodal irradiation, area of residence and institutional type and locations were all independently associated with HFRT use. Conclusion: This large Australian contemporary population‐based study demonstrates increasing use of HFRT for BC. However, large sociodemographic and institutional provider‐related variations in practice still exist.